Pengaruh Pajak, Kinerja Keuangan dan Mekanisme Bonus Terhadap Transfer Pricing - Halawa, Nevirida; Cahyani, Yenni (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to provide empirical evidence regarding the influence of tax, financial performance, and bonus mechanisms on transfer pricing practices in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Transfer pricing continues to be a central issue in corporate taxation and financial policy, particularly within sectors characterized by stable demand and frequent intra-group transactions. The sample was determined using a purposive sampling technique, resulting in 12 companies and 60 firm-year observations collected over a five-year period. Panel data regression was employed as the analytical method, and a series of model specification tests identified the Random Effect Model (REM) as the most appropriate approach. All data were processed using EViews 12 software to ensure analytical accuracy and methodological rigor. The results show that tax has a significant effect on transfer pricing with a probability value of 0.0037 < 0.05, while financial performance has no effect on transfer pricing with a probability value of 0.8811 > 0.05. The bonus mechanism also has no effect on transfer pricing with a probability value of 0.4124 > 0.05. However, when tested simultaneously, the three variables collectively have a significant effect on transfer pricing with a probability value of 0.0244 < 0.05.